Strategi Komunikasi Tokoh Adat dalam Pelestarian Budaya Butabuh Masyarakat Lampung Saibatin - Sururuzzaman, Sururuzzaman; Choiriyati, Sri; Achmadi, Achmadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study aims to identify the communication strategies of traditional leaders in preserving the Butabuh tradition among the Lampung Saibatin community in Pekon Banjar Agung, Limau District, Tanggamus Regency. The framework positions traditional leaders as the initiators of cultural transmission, linking traditional values with younger generations through communication strategies. This research employed a qualitative approach using in-depth interviews, participatory observation, and field documentation, with source triangulation to ensure data validity. The findings reveal that traditional leaders communicate cultural values through oral advice, storytelling, and by involving youth in rebana practice and traditional ceremonies. These strategies help sustain cultural continuity, although youth participation remains low due to the influence of popular culture, feelings of shyness, and lack of understanding. Preservation efforts include increasing youth engagement, utilizing social media for cultural education, and fostering collaboration between traditional leaders, the community, and local government to maintain the relevance of  Butabuh .